Performance measurements of IP over ATM and ATM API - Salamah, Muhammed; Tulgar, Tamer (My University, 2002)
The main missing part of today's ATM technology is the link between the ATM network and the applications. By using Classical IP and LAN Emulation services, it is possible to run TCP/IP based applications and emulate Ethernet, token-ring etc. on top of ATM network. With no doubt, using different protocols over an ATM network causes extra overhead and diminishes the real power of fixed sized tiny ATM cells. To overcome this overhead, various solutions proposed and a few licensed ATM APIs(Application Programming Interfaces) were developed. Some examples of these APIs can be Microsoft's Winsock-2, Marconi's (former FORE Systems) ATM API and open source ATM-On-Linux. In this paper, the main aim is to compare the performance of Eastern Mediterranean University's ATM network using ATM-On-Linux API and IP over ATM.
Proceedings of the International Conference on Telecommunications 2002 --
Keywords: ATM API; ATM on LINUX; CLIP; LANE